Análise foliar de plantas por espectrometria de emissão óptica com plasma induzido por laser (LIBS) e com plasma acoplado indutivamente após ablação com laser (LA-ICP OES) - Gomes, Marcos da Silva (Universidade Federal de São Carlos, 2013)
It has been demonstrated that laser induced breakdown spectrometry (LIBS) can be used as an alternative method for the determination of macro (P, K, Ca, Mg) and micronutrients (B, Fe, Cu, Mn, Zn) in pellets of plant materials. However, information is required regarding the sample preparation for plant analysis by LIBS. In this work, methods involving cryogenic grinding and planetary ball milling were evaluated for leaves comminution before pellets preparation. The particle sizes were associated to chemical sample properties such as fiber and cellulose contents, as well as to pellets porosity and density. The pellets were ablated at 30 different sites by applying 25 laser pulses per site (Nd:YAG@1064 nm, 5 ns, 10 Hz, 25 J cm-2). The plasma emission collected by lenses was directed through an optical fiber towards a high resolution Echelle spectrometer equipped with an ICCD. Delay time and integration time gate were fixed at 2.0 and 4.5 μs, respectively. Experiments carried out with pellets of sugarcane, orange tree and soy leaves showed a significant effect of the plant species for choosing the most appropriate grinding conditions. By using ball milling with agate materials, 20 min grinding for orange tree and soy, and 60 min for sugarcane leaves led to particle size distributions generally lower than 75 μm. Cryogenic grinding yielded similar particle size distributions after 10 min for orange tree, 20 min for soy and 30 min for sugarcane leaves. There was up to 50% emission signal enhancement on LIBS measurements for most elements by improving particle size distribution and consequently the pellet porosity. Calibration is still a challenging task when dealing with the direct analysis of solids. This is particularly true for LIBS, and laser ablation inductively coupled plasma optical xix emission spectrometry (LA-ICP OES) / mass spectrometry (LA-ICP-MS), when the calibrations are matrix-dependent and/or appropriate certified reference materials are generally not available. Looking at the analysis of plant materials in the form of pressed pellets by LIBS, a new method to overcome and/or minimize this difficulty is proposed by keeping the matrix constant in order to produce matrix-matched calibration pellets. To achieve this goal and to test this novel approach, ground sugar cane leaves were chosen and submitted to acid extractions for obtaining the corresponding blank or a material containing very low concentrations of the analytes. The resulting dried solid material was used either as a blank or a low concentration standard, and also homogeneously mixed with the original plant material at appropriate ratios as well. The corresponding pellets were used as calibration standards and ablated at 30 different sites by applying 25 laser pulses per site with a Q-switched Nd:YAG at 1064 nm. The plasma emission collected by lenses was directed through an optical fiber towards a spectrometer equipped with Echelle optics and intensified charge-coupled device. Delay time and integration time gate were fixed at 2.0 and 5.0 μs, respectively. This calibration strategy was tested for the determination of Ca, Mg, K, P, Cu, Mn, and Zn by LIBS in pellets of 17 varieties of sugar cane leaves and good correlations were obtained with inductively coupled plasma optical emission spectrometry results in the corresponding acid digests. The proposed approach was also useful to estimate the limits of detection based on measurements of blanks, as recommended by IUPAC, or with the aid of a low concentration standard. The utility of LA-ICP OES for the determination of macro- (Ca, K, P and Mg) and micronutrients (B, Mn, Fe and Zn) in plant materials is reported, for the first time. Plant leaves of orange citrus, soy and sugar cane were ground in a cutting mill and further homogenized using a high-speed ball mill for between 5 to 120 min to investigate the effect of particle size diameter on the element signal emission intensities for the analytical method. The samples were pressed into pellets for 5 min at 0.3 ton cm-2 and ablated as 10 replicates by applying 500 laser pulses per replicate. Although particle size did decrease as total mill time increased, the difference in distribution did not have a significant statistical influence on the results. The best sensitivity and precision were observed by using a fluence of 9.0 J cm-2 for the LA-ICP OES at 10 Hz. The calibration strategy was based on the use of different certified reference materials prior to pelletizing and to create calibration curves, while Sc was generally used as an internal standard in the matrix to account for any differences in laser-material interactions. Typical precision and accuracy values were determined to be <6% and 8%. Limits of detection were determined to be ~ 14 mg kg-1 Ca, 94 mg kg-1 K, 5.0 mg kg-1 Mg, 10 mg kg-1 P, 0.2 mg kg-1 B, 0.8 mg kg-1 Fe, 2.0 mg kg-1 Mn and 0.1 mg kg-1 Zn, resulting in a method that is fit for the purpose of the analysis of macro- and micro nutrients in plant material.
Foliar analysis of plants by laser induced breakdown spectroscopy (LIBS) and laser ablation inductively coupled plasma optical emission spectrometry (LA-ICP OES)
Keywords: Química analítica; LIBS; LA-ICP OES; Análise foliar; Macronutrientes; Micronutrientes; CIENCIAS EXATAS E DA TERRA::QUIMICA